DIAGNOSTIC ABNORMALITAS MENURUT ISLAM DAN PSIKOLOGI - Rismanto, Firman (Fakultas Agama Islam Universitas Muhammadiyah Bandung, 2022)
The COVID-19 pandemic has brought major changes to human life. The most visible impact on the human psyche. Restrictions on socializing provide a major change in a person's mental state. Therefore, researchers make this condition as the object of research. This study aims to discuss the diagnostic contribution that forms the basis for drawing conclusions empirically. The role of psychology aims to reduce the concepts and theories of abnormality in Islam in the form of liver disease and stress that have an impact on psychophysiological disorders during the COVID-19 period. Expert judgment from both religious experts and psychologists is needed to make behavioral aspects and indicators easily captured in the form of observations, interviews and questionnaires. The results are in the form of a descriptive report that can be tested for validity and reliability regarding abnormal behavior from both religious and psychological approaches.Keywords: diagnostic, religion, psychology